A germline MTOR mutation in Aboriginal Australian siblings with intellectual disability, dysmorphism, macrocephaly, and small thoraces. (6th April 2015) - Baynam, Gareth; Overkov, Angela; Davis, Mark; Mina, Kym; Schofield, Lyn; Allcock, Richard; Laing, Nigel; Cook, Matthew; Dawkins, Hugh; Goldblatt, Jack
<x xml:space="preserve">Abstract</x> We report on three Aboriginal Australian siblings with a unique phenotype which overlaps with known megalencephaly syndromes and RASopathies, including Costello syndrome. A gain‐of‐function mutation in MTOR was identified and represents the first reported human condition due to a germline, familial MTOR mutation. We describe the findings in this family to highlight that (i) the path to determination of pathogenicity was confounded by the lack of genomic reference data for Australian Aboriginals and that (ii) the disease biology, functional analyses in this family, and studies on the tuberous sclerosis complex support consideration of an mTOR inhibitor as a therapeutic agent. © 2015 Wiley Periodicals, Inc.